(3jJjeI GdOgQ aj eMGSf Cgd GdYUQs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NjQ eG HOF Hg Gdcde hNJe CeG HYO aEf eMGSf CUfGa GdCOH cKjQI , hfcJgG bdjdI hEfJgRJ QbOI ef Yjf GdReGf hGSJeQQJ ai JbQjQ gPg GdfSNI GdCNjQI s
(3BNQgG (B:s
(3BNQg BNQ GdHGH GdYGTQ efGdbSe GdKGfi ai JQLeI GdTQja GdQVi (B: (3haNQ GdaJi HGdbhd dGHfTjOg hjQhi adGf eQg hadGf s
(3GdeLdO GdChd hjTJed GdbSejf GdChd hGdKGfis
(3cJHJ HYV cdeGJgG HGdMeQIs
(3Ydi GdfSNI JedcGJ CbOegG SfI (B1170 s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdCOHs